PERENCANAAN SUKSESI PADA PERUSAHAAN KELUARGA (Studi Fenomenologi Pada Perusahaan Keluarga Arya Mas) - Amarila Tungga Dewi; Indi Djastuti (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
Family firms are important assets that must be maintained for their sustainability. Therefore, the founder of the company should give extra attention to seek the succession of leadership for the company to continue sustainably with the right successor based on the criteria of the company. The purpose of this study is to determine whether the successor is appropriate according to company criteria or not if it is seen from the criteria of communication, personality, leadership, and the successor motivation.The method that will be used in this research is descriptive qualitative method with interview and observation as data collection technique. This research was conducted in Arya Mas Salatiga family company, with purposive sampling as the method of determining the resource, and member check as the test of the validity of the data.The results of this study indicate that the successor is already match or suitable with the criteria proposed by the company. Successors can communicate well and are in conformity with the criteria of the big 5 models and criteria of ACEMAN leaders although there are 1 unfulfilled criteria, as well as the high motivation and support of the founders in the training and development of the successor to make the successor worthy of being the leader of the company.